Effect of Steaming Time on The Protein Quality and Functional Properties of Soybean Paste - Natasya Crisly; Lucia Crysanthy Soedirga (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2026)
Thermal processing is essential for enhancing the nutritional quality and protein digestibility of soybeans. Steaming, which uses hot vapor to minimize direct contact between the food and water, as in boiling, thereby better preserves nutrient content. However, excessive heating can decrease the quality and functional properties of the protein; therefore, the selected cooking time, specifically the steaming time, must be determined. This study investigated the effects of varying steaming times (25, 40, and 55 minutes) on the protein quality—specifically protein content and in-vitro protein digestibility—and functional properties, including emulsion stability and water holding capacity, of soybean paste. Results indicated that prolonged steaming significantly reduced both protein quality and functional properties. Extended thermal exposure resulted in excessive protein denaturation and aggregation, thereby disrupting the structural integrity required for effective water binding and emulsion stabilization. The selected steaming time was 25 minutes, yielding a protein content of 29.62 ± 1.10% and an in vitro protein digestibility of 44.40 ± 0.36%. Furthermore, at this selected steaming time, the soybean paste exhibited the highest emulsion stability and water holding capacity values of 92.79±1.76% and 71.25±1.77%, respectively. These findings support SDG 2 (Zero Hunger), SDG 3 (Good Health and Well-being), and SDG 12 (Responsible Consumption and Production) by establishing a resource-efficient method for producing high-quality, sustainable plant-based proteins. This 25-minute steaming duration establishes a standardized approach to enhancing the nutritional and functional profiles of soybean-based ingredients.